Object Clauses in Academic Discourse: Genre Preferences - Steksova, Tatiana Ivanovna (Жанры речи, 2020)
The author of the article understands object clauses as a semantic type of sentences with a set of different ways of expressing semantics: polypredicative subordinate clauses, asyndetic clauses, monopredicative clauses, clauses with parenthesis. It is suggested that the set of constructions used in academic discourse depends on the genre of the academic text. The genres of article abstracts and thesis summaries as secondary texts (texts about texts) were chosen as a material for a comparative study. The author reveals the incomplete paradigm of object clauses in secondary academic texts. The analyzed language material allows us to state that the genre of the academic article abstract does not use the entire paradigm of the ways of expressing explanatory semantics, choosing only two models as the basic ones, with a higher frequency of the monopredicative model. In the genre of thesis summaries there is a lower frequency of monopredicative clauses with deliberative semantics and a higher frequency of polypredicative subordinate clauses containing hidden reflection of the author of the text. The analyzed material indicates that the hidden author’s reflection is more often manifested through the use of quasi-impersonal sentences. The author of the article believes that there is a tendency in the analyzed genres towards increasing impersonality, the elimination of the subjective author’s position, and the desire to objectify the presented information. The research has found out certain constructions which function actively in the genre of the academic article, but are not used in article abstracts and thesis summaries. It is noted that not all introducing predicates recorded in the academic literature function in the analyzed genres. This can be explained by the genre affiliation of the texts and their communicative task. The author determines a number of objectives of the further research.